Medullary astrocytes mediate irregular breathing patterns generation in chronic heart failure through purinergic P2X7 receptor signalling - Toledo, Camilo; Diaz-Jara, Esteban; Diaz, Hugo S.; Schwarz, Karla G.; Pereyra, Katherin; Las Heras, Alexandra; Rios-Gallardo, Angelica; Andrade, David C.; Moreira, Thiago; Takakura, Ana; Marcus, Noah J.; Del Rio, Rodrigo (My University, 2022)
Background Breathing disorders (BD) (apnoeas/hypopneas, periodic breathing) are highly prevalent in chronic heart failure (CHF) and are associated with altered central respiratory control. Ample evidence identifies the retrotrapezoid nucleus (RTN) as an important chemosensitivity region for ventilatory control and generation of BD in CHF, however little is known about the cellular mechanisms underlying the RTN/BD relationship. Within the RTN, astrocyte-mediated purinergic signalling modulates respiration, but the potential contribution of RTN astrocytes to BD in CHF has not been explored. Methods Selective neuron and/or astrocyte-targeted interventions using either optogenetic and chemogenetic manipulations in the RTN of CHF rats were used to unveil the contribution of the RTN on the development/maintenance of BD, the role played by astrocytes in BD and the molecular mechanism underpinning these alterations. Findings We showed that episodic photo-stimulation of RTN neurons triggered BD in healthy rats, and that RTN neurons ablation in CHF animals eliminates BD. Also, we found a reduction in astrocytes activity and ATP bioavailability within the RTN of CHF rats, and that chemogenetic restoration of normal RTN astrocyte activity and ATP levels improved breathing regularity in CHF. Importantly, P"X/ P2X7 receptor (P2X7r) expression was reduced in RTN astrocytes from CHF rats and viral vector-mediated delivery of human P2X7 P2X7r into astrocytes increases ATP bioavailability and abolished BD. Interpretation Our results support that RTN astrocytes play a pivotal role on BD generation and maintenance in the setting CHF by a mechanism encompassing P2X7r signalling. Copyright (c) 2022 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)
Keywords: chronic heart failure; disordered breathing; astrocyte; retrotrapezoid nucleus; p2x7 receptor